Shift and night work and long working hours – a systematic review of safety implications - Wagstaff, Anthony Sverre; Sigstad Lie, Jenny-Anne (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVE ': 'In order to devise effective preventive strategies, it is important to study workplace stressors that might increase the risk of workplace accidents − both affecting workers themselves as well as causing harm to third-parties. The aim of this report is to provide a systematic, updated overview and scientific review of empirical research regarding accidents in relation to long work hours and shift work, primarily based on epidemiological studies. ' ' METHODS ': 'The search for articles was part of a large review study on the effects of work hours on various health outcomes, safety, and performance. The search strategy included 5 international scientific databases, and nearly 7000 articles were initially identified using our search string. Following the application of inclusion and exclusion criteria, 443 publications were found and evaluated using a pre-defined scoring system. Of these, 43 concerned safety and accidents but only 14 were considered to be of high quality (total score 2 or 3 on a scale from 0−3) and therefore used for this study. ' ' RESULTS ': 'Both shift work and long working hours present a substantial and well-documented detrimental effect on safety − all the studies that are included in this review have one or more significant findings in this respect. The trends are quite coherent although the increases in accident rates are mostly from 50% to 100%. In epidemiological terms, this may be seen as rather small differences. The use of such data is therefore only of importance if the accident incidence is high or if accidents may have large effects. ' ' CONCLUSIONS ': 'The findings are most relevant to safety-critical activities such as the transport and health sectors. Work periods >8 hours carry an increased risk of accidents that cumulates, so that the increased risk of accidents at around 12 hours is twice the risk at 8 hours. Shift work including nights carries a substantial increased risk of accidents, whereas “pure” night work may bring some protection against this effect due to resynchronization. The evaluated studies give no clear indications of any age or gender being specifically susceptible or protected against the effects of work times scheduling on accident risk.
Keywords: accident; long working hours; night work; safety; shift work; systematic review